2020
DOI: 10.1371/journal.pone.0222689
|View full text |Cite
|
Sign up to set email alerts
|

AIRE is induced in oral squamous cell carcinoma and promotes cancer gene expression

Abstract: Autoimmune regulator (AIRE) is a transcriptional regulator that is primarily expressed in medullary epithelial cells, where it induces tissue-specific antigen expression. Under pathological conditions, AIRE expression is induced in epidermal cells and promotes skin tumor development. This study aimed to clarify the role of AIRE in the pathogenesis of oral squamous cell carcinoma (OSCC). AIRE expression was evaluated in six OSCC cell lines and in OSCC tissue specimens. Expression of STAT1, ICAM1, CXCL10, CXCL11… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…34,35 Overexpression of STAT1 was observed in many SCCs and can promote the malignant ability of SCC. [36][37][38] Our findings suggested that TP63 and STAT1 may play a critical role in CSCC, and more studies on their mechanisms are necessary for the future.…”
Section: Discussionmentioning
confidence: 79%
“…34,35 Overexpression of STAT1 was observed in many SCCs and can promote the malignant ability of SCC. [36][37][38] Our findings suggested that TP63 and STAT1 may play a critical role in CSCC, and more studies on their mechanisms are necessary for the future.…”
Section: Discussionmentioning
confidence: 79%
“…AIRE, the autoimmune regulator, plays a key role in shaping central immunological tolerance by facilitating the negative selection of T cells. AIRE has been associated with the polyglandular syndrome type 1 (APS1) [40] and with cancer [41][42][43]. According with the literature [44] and with PROMO, a virtual laboratory for the identi cation of putative transcription factor binding sites, ERK1/2, which is linked to PRKC , activates Ets and Elk1 potential TF for AIRE.…”
Section: Discussionmentioning
confidence: 99%
“…AIRE is a transcription factor expressed by thymic ( Anderson et al., 2002 ) and extrathymic ( Poliani et al., 2010 ) cells, including stromal ( Bergström et al., 2019 ) and circulating ( Suzuki et al., 2008 ) elements, displaying features shared with dendritic cells (DCs) and therefore critically implicated in central tolerance. Intriguingly, animal models ( Zhu et al., 2013 ) and human studies ( Nguyen et al., 2020 ; Kalra et al., 2018 ) have pointed to a regulatory role of AIRE in cancer immune surveillance. However, this contention cannot be widely applied to a variety of neoplastic diseases since conflicting results have been reported ( Klamp et al., 2006 ).…”
Section: Sexual Dimorphism In Immune Responsementioning
confidence: 99%